Evaluation of Real-Time Quaking-Induced Conversion, ELISA, and Immunohistochemistry for Chronic Wasting Disease Diagnosis - Holz, Carine L.; Darish, Joseph R.; Straka, Kelly; Grosjean, Nicole; Bolin, Steven; Kiupel, Matti; Sreevatsan, Srinand (Frontiers in Veterinary Science, 2022)
Chronic wasting disease (CWD) is a transmissible prion disorder, primarily affecting free-ranging and captive cervids in North America (United States and Canada), South Korea, and Europe (Finland, Norway, and Sweden). Current diagnostic methods used in the United States for detection of CWD in hunter harvested deer involve demonstration of the causal misfolded prion protein (PrPCWD) in the obex or retropharyngeal lymph nodes (RLNs) using an antigen detection ELISA as a screening tool, followed by a confirmation by the gold standard method, immunohistochemistry (IHC). Real-time quaking-induced conversion (RT-QuIC) assay is a newer approach that amplifies misfolded CWD prions in vitro and has facilitated CWD prion detection in a variety of tissues, body fluids, and excreta. The current study was undertaken to compare ELISA, IHC, and RT-QuIC on RLNs (n = 1,300 animals) from white-tailed deer (WTD) in Michigan. In addition, prescapular, prefemoral and popliteal lymph nodes collected from a small subset (n = 7) of animals were tested. ELISA and RT-QuIC detected PrPCWD in 184 and 178 out of 1,300 RLNs, respectively. Of the 184 ELISA positive samples, 176 were also IHC positive for CWD. There were seven discordant results when comparing IHC and ELISA. RT-QuIC revealed that six of the seven samples matched the IHC outcomes. One RLN was negative by IHC, but positive by ELISA and RT-QuIC. RT-QuIC, IHC, and ELISA also detected PrPCWD in prescapular, prefemoral and popliteal lymph nodes. Taken together, we show evidence that the RT-QuIC assay is well-suited for routine CWD diagnostics and could potentially replace ELISA and/or IHC in CWD surveillance programs. RT-QuIC also demonstrated that CWD prions are distributed across lymph nodes in a variety of anatomic locations. A multi-laboratory validation on blinded sample panels is underway and is likely to help to provide insight into the variability (lab-to-lab), analytical sensitivity, and specificity of gold standard diagnostics versus RT-QuIC assay.